Seismic vulnerability assessment of historical urban centres: The case study of campi alto di norcia, Italy - Romis, F. (2020)
Seismic damage assessment is a valuable opportunity to evaluate the accuracy of vulnerability and risk methodologies applied to historic masonry buildings, giving the possibility of enhancing and optimizing mitigation and retrofit strategies. Vulnerability index methodologies are flexible and powerful tools for the seismic assessment at urban scale, able to provide a first screening of the critical issues present in masonry structural aggregates. The different structural features of the buildings, directly and indirectly influencing their structural behaviour, are measured through different weights and scores finally achieving a vulnerability indicator. In the present paper, four different vulnerability index methodologies are applied to the medieval city of Campi Alto di Norcia in Valnerina, Umbria, recently stroke by the 2016 Central Italy earthquakes. The accuracy of the adopted Iv methods is assessed based on the real damages' analysis performed in the surrounding area, comparing results achieved from the application of considered methodologies to direct in-situ observations. Data collected during the 2016 post-earthquake damage surveys and usability assessment, together with the external visual inspections carried out and with the information coming from retrofitting design interventions performed between 1979 and 1997, are used.